PASSIVELY Q-SWITCHED YTTERBIUM-DOPED FIBER LASER EMPLOYING SAMARIUM OXIDE AS SATURABLE ABSORBER - Mohd Rusdi, Muhamad Khairul Nizam; Jafry, Afiq Arif Aminuddin; Zulkifli, Nur Farhanah; Mohamad Samsamnun, Farina Saffa; Mahyuddin, Mohamad Badrol Hisyam; HARUN, SULAIMAN WADI; Zainal Abidin, Mohd Shahnan; Saidin, Norazlina (IIUM Engineering Journal, 2020)
The rapid developments in transition metal dichalcogenide materials as a saturable absorber (SAs) have been demonstrated to be an effective method for generating Q-switched fiber laser. This work, reports on the generation of Q-switched fiber laser in the 1-micron region using samarium oxide (Sm2O3) saturable absorber (SA). The Sm2O3 thin film SA was fabricated in- The rapid developments in transition metal dichalcogenide materials as saturable absorbers (SAs) have been reported to be efficient materials for generating Q?switched fiber lasers. In this paper, we report on the use of samarium oxide (Sm2O3) saturable absorber (SA) for 1-micron Q-switched fiber laser generation. The Sm2O3 thin film SA was constructed in-house through which the Sm2O3 powder was mixed and stirred in polyvinyl alcohol (PVA) solution. It was then integrated into the ytterbium-doped fiber laser (YDFL) ring cavity, hence producing a sequence of Q-switched pulsed lasers at 1062.49 nm wavelength. The stable pulse train appeared from 69.97 to 111.1 kHz between the applied pump power of 57 mW to 96 mW. The signal-to-noise ratio (SNR) of 38.56 dB was recorded at the 57 mW pump power, whereas the pulse energy raised until 15.21 nJ at 96 mW. These results showed that the Sm2O3 could be a favourable SA material to iniatiate Q-switched ytterbium-doped pulsed fiber laser. ABSTRAK: Perkembangan pesat dalam bahan logam peralihan dichalcogenide sebagai bahan penyerap boleh larut (SAs) telah dilaporkan sebagai kaedah yang berkesan bagi menjana laser fiber Q-switched. Kajian ini menggunakan samarium oksida (Sm2O3) saturable absorber (SA) bagi menjana laser gentian Q-switched 1-Micron. Filem nipis Sm2O3 SA telah dihasilkan melalui campuran serbuk Sm2O3 ke dalam cecair polivinil alkohol (PVA) dalam persekitaran makmal. Kemudian, ia diintegrasi ke dalam rongga gelang laser gentian dop-ytterbium (YDFL), lalu menghasilkan denyut laser Q-switched stabil pada jarak gelombang 1062.49 nm. Denyutan stabil muncul dari 69.97 kepada 111.1 kHz pada kuasa pam yang dikenakan antara 57 mW hingga 96 mW. Nisbah isyarat-hinggar (SNR) pada 38.56 dB telah direkodkan pada pam kuasa 57 mW, sementara denyut tenaga ditingkatkan kepada 15.21 nJ pada 96 mW. Keputusan menunjukkan Sm2O3 merupakan bahan SA penggalak yang memuaskan bagi menjana denyut laser gentian dop-ytterbium Q-switched. house. It was integrated into the ytterbium-doped fiber laser (YDFL) ring cavity, hence producing a stable passively Q-switched laser operating at 1062.49 nm wavelength. Stable pulse train appeared from 69.97 to 111.1 kHz at the tunable pump power of 57 mW to 96 mW. The pulse energy of up to 15.21 nJ and signal-to-noise ratio (SNR) of 38.56 dB for the fundamental frequency were recorded. The results showed that the Sm2O3 could be a favourable SA material for the broadband generation of Q-switched fiber laser.